Curcumin Facilitates Aryl Hydrocarbon Receptor Activation to Ameliorate Inflammatory Astrogliosis - Chun-Hua Lin; Chia-Cheng Chou; Yi-Hsuan Lee; Chia-Chi Hung (Molecules, 2022)
Curcumin is an anti-inflammatory and neuroprotective compound in turmeric. It is a potential ligand of the aryl hydrocarbon receptor (AhR) that mediates anti-inflammatory signaling. However, the AhR-mediated anti-inflammatory effect of curcumin within the brain remains unclear. We investigated the role of AhR on the curcumin effect in inflammatory astrogliosis. Curcumin attenuated lipopolysaccharide (LPS)-induced proinflammatory IL-6 and TNF-α gene expression in primary cultured rat astrocytes. When AhR was knocked down, LPS-induced IL-6 and TNF-α were increased and curcumin-decreased activation of the inflammation mediator NF-κB p65 by LPS was abolished. Although LPS increased AhR and its target gene CYP1B1, curcumin further enhanced LPS-induced CYP1B1 and indoleamine 2,3-dioxygenase (IDO), which metabolizes tryptophan to AhR ligands kynurenine (KYN) and kynurenic acid (KYNA). Potential interactions between curcumin and human AhR analyzed by molecular modeling of ligand–receptor docking. We identified a new ligand binding site on AhR different from the classical 2,3,7,8-tetrachlorodibenzo-p-dioxin site. Curcumin docked onto the classical binding site, whereas KYN and KYNA occupied the novel one. Moreover, curcumin and KYNA collaboratively bound onto AhR during molecular docking, potentially resulting in synergistic effects influencing AhR activation. Curcumin may enhance the inflammation-induced IDO/KYN axis and allosterically regulate endogenous ligand binding to AhR, facilitating AhR activation to regulate inflammatory astrogliosis.